Application of Structural Equation Modelling To Analyse the Environmental Impact of Sustainable Manufacturing Implementation - Keshav Ganpatrao Valase; D. N. Raut (International Journal of Supply Chain Management, 2018)
Structural Equation Modelling (SEM) has wide applications, but still very little research has been carried out in the field of its applications to Sustainable Manufacturing (SM), which is a vital concern of the Supply Chain Management (SCM) issues in todays competition. There is a need of integrated and more comprehensive approach for the implementation of SM with due importance to manufacturers perceptions towards the decision making issues related to manufacturing and technology domains. The paper addresses this need with primary focus on SM implementation with a new framework based on domains of Manufacturing and Technology, Environmental, Social, Economical. Partial Least Square Structural Equation Modelling (PLS-SEM) approach has been used for the analysis of empirical data collected from 72 engineering manufacturing industries from India. The model fit analysis revealed quite satisfactory results for manufacturing and technology domain in addressing environmental concerns and a need to enhance the focus on social domain. Authors expect that this study will provide wide openings for the application of SEM model for the enhancement of SM, in various geographical regions across the globe.